Investigação da acalásia do esfíncter anal interno por meio da eletromanometria de pacientes chagásicos obstipados com e sem megacolo (Goiânia-Goiás-Brasil) - ALMEIDA, Arminda Caetano de (2012)
Chagas disease remains as an important public health challenge in South America. The Chagas colopathy is considered the second clinical digestive manifestation most common of the disease and constipation chronic, its main symptom. The general objective was to investigate the presence of achalasia, through electromanometry of the internal anal sphincter, in constipated chagasic patients with and without megacolon. This study evaluated clinical and electromanometry parameters of 64 patients with symptoms of constipation, attended on the service of coloproctologya on a university hospital in Brazil, central region. The achalasia was present in 91.3% (IC95% 74.13 to 98.52) of patients with megacolon and/or megarecto (Group 1), in 47.29% (IC95% 27.29 to 68.57) without megacolon and/or megarecto (Group2), and was not present in patients of the control group (Group 3). The rectal capacity was 309.1, 159.2 and 150.1 ml in the groups 1, 2 and 3 respectively. In conclusion the electromanometry detects achalasia of the internal anal sphincter in almost totality of patients with megacolon and/or megarecto. The megacolon presence in constipated patients with Chagas Disease alert to the possibility of occurrence of achalasia on the internal anal sphincter. In chronically constipated patients with positive serology for Chagas Disease, without megacolon the a finding of absence of the recto anal inhibitory reflex, by electromanometry, can definitively prove the Chagas colopathy, while the presence of reflection departs, at the time, this diagnosis, should these patients be followed and treated like other patients with constipation due to other causes The comparison of clinical manifestations in the three groups not evidenced differences that could distinguish patients with Chagas colopathy those with functional constipation, reaffirming the importance of holding the electromanometry in Chagasic and constipated patients.